A new species of the rare genus Myroconger Günther, 1870 (Anguilliformes: Myrocongridae) from Brazilian waters, tropical western Atlantic - Espíndola, Vinicius C.; Caires, Rodrigo A.; Tighe, Kenneth A.; Pinna, Mario C. C. De; de Melo, Marcelo R. S. (Zootaxa, 2021)
The family Myrocongridae comprises some of the rarest and least known benthopelagic eel species. It is composed of a single genus, Myroconger Günther, 1870, and five valid species: M. compressus Günther, 1870, from the Atlantic Ocean; M. gracilis Castle, 1991, M. prolixus Castle & Béarez, 1995, and M. nigrodentatus Castle & Béarez, 1995, from the Pacific Ocean; and M. seychellensis Karmovskaya, 2006, from the Indian Ocean. Herein, we report on an additional species from the Atlantic Ocean, Myroconger pietschi n. sp., based on a specimen obtained on the Aracati Bank, North Brazilian ridge, off Ceará State, western South Atlantic. Myroconger pietschi can be diagnosed by having 190 anal-fin rays, a short pectoral fin (16.6% HL), the posterior portion of the ethmovomerine teeth arranged in a single row, teeth on lower and upper pharyngeal tooth plate 24 and 27, and 10 branchiostegal rays.